Discourse, Discourse Everywhere: Subject "Agency" in Feminist Discourse Methodology - Bacchi, Carol (NORA : Nordic journal of women's studies, 2005)
The purpose of this article is to provoke much-needed discussion on the uses by feminists, in particular feminist political scientists, of the language of discourse, discourses and discursive. The terms, it argues, have become ubiquitous, with considerable confusion about intended meanings. A particular concern is the growing tendency among some feminist political scientists to use "discourse" as shorthand for ways of talking about an issue. Critical to sorting through different meanings of discourse, it argues, is the question of subject "agency"-the extent to which subjects can use discourses or are constituted by them. As a way forward the article advances a dual-focus agenda that builds bridges across discourse traditions; identifying both the ways in which interpretive and conceptual schemas delimit understandings, and the politics involved in the intentional deployment of concepts and categories to achieve specific political goals.